“Comparativo de rendimiento de seis variedades de soya (glycine max. (L) Merril) en el Huallaga central Región San Martín” - Zegarra López, Luis Ernesto (2002)
With the purpose of determining the varieties of yield and adaptation, with characteristic agronomic desirable for the Central Huallaga; he/she put on in execution a experiment comparative of six varieties of Soya, all them proceedings from Bolivia; reaching the potential maximum of yield the variety IAC-8C with 4230.47 Kg./he of grain, without to be able to find difference signíficant statistic wíth the varieties OCEPAR-9, CRYSTALLINE-T, IAC-8, CRYSTALLINE with 3709.35, 3621.12, 3585.94, 3375.00 Kg/he respectively. The experiment in mention was carried out in the District of Caspizapa, Province of Picota, Region San Martín, in a soil Vertisol, fine texture, Potassium and Phosphorus middle, high saturation of bases. The disposition of the used experiment was at random of Complete Block with four repetitions, eight furrows twins and between plant to 0.20 m, being obtained a population of 300000 plants by hectare, with an equivalent use to 80 Kg of seed for hectare. A fertilízation was made via foliating being used Phosphate Monoamónico whose contribution was of 12% of N and 61% of P20s, beíng that according to the result of the chemical analysis, Phosphorus and Potassium · with meddle availability , the application was carried out when the plants had two couples of leaves. The nodulatio~ had a significant increase in the main and lateral root to the moment of the one filled of sheaths, but in general there was little nodulation due mainly to the used it inoculate that it didn't act like it was expected. The varieties that showed to be more precocious in relation to the days to flourish were IAC-8C (42 days), and in the maturation stage OCEPAR-9 (104 days). The variety IAC - 8C with 10.1 O cm obtained the biggest height of next sheath to the floor and the CRYSTALLINE variety obtained the smallest height with 5.60 cm. In the number of sheaths for plant the variety OCEPAR - 9 with 82.63 sheaths for plant occupied the first place and the variety IAC - 8C the last place with 64 sheaths for plant; while in the weight of a hundred seeds the variety IAC - 8C with 21.29 gr. obtained the biggest weight and the variety EMGOPA- 308 with 15.82 gr. occupied the last place. In the economic analysis The variety IAC - 8C obtained a net entrance of SI. 2549.51 representing a profitability of 67.16% and a relationship benefits cost of 1.67.